2020
DOI: 10.3389/fpubh.2020.583455
|View full text |Cite
|
Sign up to set email alerts
|

Combining Microfinance and Health in Reducing Poverty-Driven Healthcare Costs: Evidence From the Philippines

Abstract: The role of microfinance in alleviating poverty and poor health is significant. Its health programs have been shown to improve healthcare utilization and strengthen a healthcare system. In the Philippines, microfinance's widespread presence is seen as instrumental in achieving the objectives of Healthy Philippines 2022 , particularly in reducing poverty-driven healthcare costs. However, little is known on how microfinance can reduce the cost of healthcare services and treatment. Also, fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Microfinance schemes may thus be used for priming participants to the behaviour of regular payments when designing and implementing the forthcoming NHIS. Studies in the Phillipines have observed that microfinance schemes when combined with health can enhance service delivery and uptake of policies [ 18 ]. In Kenya microfinance schemes have put in place health care financing schemes which provide access to preventive and curative health services as well as financing in form of health saving plans and emergency health loans for the poor [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microfinance schemes may thus be used for priming participants to the behaviour of regular payments when designing and implementing the forthcoming NHIS. Studies in the Phillipines have observed that microfinance schemes when combined with health can enhance service delivery and uptake of policies [ 18 ]. In Kenya microfinance schemes have put in place health care financing schemes which provide access to preventive and curative health services as well as financing in form of health saving plans and emergency health loans for the poor [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…This prepayment mechanism is particularly useful for cushioning households from catastrophic poverty, injury and death resulting from treatable and chronic diseases [14][15][16][17]. Studies show that microfinance schemes could potentially act as intermediaries in this effort as they could put in place financing mechanisms which favour a reduction in healthcare costs for their members [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…However, MFIs are rarely used to fund healthcare start-ups, and are instead used to pay for healthcare. 46 Many caveats exist with MFIs. MFIs are established on the premise that impoverished business owners will eventually make sufficient profit to be able to pay back the loan with a high level of interest.…”
Section: Microeconomic Perspectivementioning
confidence: 99%
“…This venture model provides entrepreneurs with initial working capital, which individuals can then pay back when their business grows to a substantial enough size to afford the repayments. However, MFIs are rarely used to fund healthcare start‐ups, and are instead used to pay for healthcare 46 …”
Section: Challenges Of Making Mri More Availablementioning
confidence: 99%
“…Thus, emphasizing the need to extend PhilHealth's coverage to the poor and to anyone with greater need of assistance. Aranas et al (2020) studied the importance of microfinancing in the Philippines and found that microfinancing plays a significant role in the improvement of poverty, health situations, and out-of-pocket healthcare expenditure of the country and is foreseen to be of big help in attaining the objectives of Healthy Philippines 2022. Aside from microfinance, health loans and microinsurance can also help reduce healthcare costs.…”
Section: Deaths Disaster Management and Healthcarementioning
confidence: 99%